Belgium : Financial System Stability Assessment-Technical Note-Banking, Insurance, and Financial Conglomerate Supervision. (IMF Staff Country Reports; Country Report, 2018)
This Technical Note analyzes the key aspects of the regulatory and supervisory regime of banks, insurance companies and financial conglomerates (FCs) in Belgium. The regulatory framework for Belgian financial institutions has been strengthened substantially since the 2013 Financial Sector Assessment Program. Notably, new national banking and insurance laws have been issued, the Bank Recovery and Resolution Directive and amendments to Financial Conglomerate Directive have been transposed, Solvency II has been implemented, and the National Bank of Belgium has been designated as the macroprudential authority. This has improved significantly the regulatory framework and broadened its scope to better address the challenges posed by FCs. Financial sector supervision has also been upgraded markedly.